The role of input in learning english in an immersion context: a case study - SANTOS, Joice Keleen Ribeiro (2023)
The need for people to learn other languages is not recent. To this end, a very wide variety of methods and techniques have been studied and applied in various contexts seeking bilingualism and multilingualism. Among these, the immersion method stands out for being practical and active, where the student will spend as much time as possible in contact with the target language. In this sense, some schools offer the opportunity to acquire a second language through the content. However, most people in Brazil do not have opportunity to study in bilingual schools. In fact, studies on the immersion method in this country and the need to provide the foreign language learner with input are still scarce. This paper aims to demonstrate through a case study the development of a 10 years old child in an immersion context in the acquisition of a foreign language (English) through her sister. From the theories demonstrated during the work and the placement test that seeks to evaluate the subject's English level on an international scale and observation table, it was exposed the child's development in terms of input (comprehension), output (oral production) and structures produced by the subject.